Global environmental governance - considerations for a way forward for the Commonwealth - Yusuf, Nageela (Commonwealth Policy Studies Unit [London]GB, 2009)
Offers a general review of the debate surrounding the reform of global environment governance (GEG). Seeks to consider the role that Commonwealth Environment Ministers could play in driving the agenda for effective global environmental governance; GEG leadership and the greater role non-state actors could play in the development of GEG policy and policy implementation.